Invasive Saprochaete Infections: An Emerging Threat to Immunocompromised Patients - Said El Zein (Pathogens, 2020)
Saprochaete clavata and Saprochaete capitata are emerging fungal pathogens that are responsible for life threatening infections in immunocompromised patients, particularly in the setting of profound neutropenia. They have been associated with multiple hospital outbreaks mainly in Europe. In this article, we present a comprehensive review of the epidemiology, clinical presentation, diagnosis, antifungal susceptibility and treatment of these organisms. The diagnosis of invasive Saprochaete disease is challenging and relies primarily on the isolation of the fungi from blood or tissue samples. Both species are frequently misidentified as they are identical macroscopically and microscopically. Internal transcribed spacer sequencing and matrix-assisted laser desorption ionization-time of flight mass spectrometry are useful tools for the differentiation of these fungi to a species level. Saprochaete spp. are intrinsically resistant to echinocandins and highly resistant to fluconazole. Current literature suggests the use of an amphotericin B formulation with or without flucytosine for the initial treatment of these infections. Treatment with extended spectrum azoles might be promising based on in vitro minimum inhibitory concentration values and results from case reports and case series. Source control and recovery of the immune system are crucial for successful therapy.